Algorithms for the computer simulation of ultrafast photoinduced intermolecular charge transfer in liquids - Feskov, S.V.; Khokhlova, S.S. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2020)
Efficient approaches to the numerical solution of equations describing the kinetics of two-stage photochemical reactions in a viscous polar solvent are proposed. The mathematical model is based on the extended integral encounter theory and takes into account diffusive mobility of reactants in solution, nonequilibrium of solvent and intramolecular degrees of freedom, and remote electron transfer in solvent-separated donor-acceptor pairs. In the framework of the Brownian simulation technique, a number of numerical algorithms for calculating unreactive stochastic trajectories of particles on free energy surfaces corresponding to different electronic states of reactants and products are suggested, some computational schemes for the detection of reaction events and the generation of electronic hops are developed, and algorithms for calculating the time-dependent reaction fluxes between the electronic states and integral kernels of the kinetic equations are implemented. The results of test simulations demonstrating the validity of the numerical solutions and reproducing well-known features of electron transfer reactions in polar solvents are discussed.